Aprendamos juntos Cuaderno de trabajo. Primera parte. - Instituto Nacional para la Educacion de los Adultos, Mexico City (Mexico).; Instituto Nacional para la Educacion de los Adultos, Mexico City (Mexico). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
This workbook is part of a Mexican series of instructional materials designed for Spanish speaking adults who are in the process of becoming literate or have recently become literate in their native language. This workbook focuses on teaching initial sounds and letters and moves on to simple words and sentences. The unit on mathematics goes over simple numeracy. The workbook units are organized around Spanish vowels and sounds in common spanish words, such as pinata, tortilla, and casa. (Adjunct ERIC Clearinghouse for ESL Literacy Education) (CK)
ERIC Note: For a related series, see FL 801 047-065.
Teachers.
Students.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Adult Literacy; Course Content; Foreign Countries; Independent Study; Instructional Materials; Native Language Instruction; Skill Development; Spanish Speaking; Vocabulary Development; Writing Skills; Mexico; Guides, Classroom -- Learner